Physical-structural properties of soil in an area under degradation process near the margins of the Balsas-MA river (Research, Society and Development, 2022)
It is notable that in recent years, there is an increasing recurrence of anthropic activities that directly or indirectly impact environmental areas. Based on this, this paper aims to present data from a particular area near the neighborhood Trizidela in the municipality of Balsas-MA that is in the process of degradation that is located on the banks of the Balsas River, presenting a survey of data and information about the physical and structural properties of the soil under study. The work carried out has a quali-quantitative evaluative type methodology and the analysis of the results was done in order to expose the existing interrelationships between the physical-structural properties of the soil, the evaluation of the structural quality and the rapid diagnosis of soil structure (DRES), obtaining as a basis for understanding the processes of environmental degradation present in the area. As main results, we highlight the evaluation of the physical-structural properties of the soil that indicates a superior physical and structural quality for point P1, considerably more conserved. However, the data for points P2 and P3 did not show the severity of the degradation observed at the site, requiring further analysis in relation to the other soil attributes and properties and even by different methods. Through the ESRD, it was possible to prove the superior structural quality of the collection point P1 in relation to P2 and P3, but different from the evaluation of the physical-structural attributes, it showed the advanced degradation that these last two points are.